Dog stories in basic vocabulary - Dolch, Edward William 1889-1961.; Dolch, Marguerite Pierce 1891-.; Johnson, Bernette; Kerr, Robert S. (Champaign, Ill. Garrard Press, 1954)
Dog stories, based on newspaper or other news reports, about a sheep dog, fire house mascots, children's pets, and others, many of which performed heroic deeds.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Short stories